Zaginięcia kryminalne, czyli szukanie śladów po latach - Stojer-Polańska, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
This article concerns the problem of criminal disappearances when the absence of a victim is caused by a criminal act conducted by an offender. The reasons of disappear-ance may be due to murder and this fact can occur after some years. Even after many years, it is possible to find forensic traces, work with witnesses and determine the motive for the crime.
Keywords: zaginięcia; poszukiwanie osób zaginionych